Malaysian student’s attitude towards organic food buying behaviour - Busari, Saheed Abdullahi (2021)
The primary purpose of this study is to investigate the key determinants and their impact on the organic food purchase intentions of the university students in Kuala Lumpur, Malaysia. Random sampling was carried out of 329 university students and quantitative questionnaire data was generated to inform the research about their attitude towards organic food. Multiple regression analyses show four determinants have significant influence on purchase intention. This study found out that environmental concern, convenience and price, subjective norms, religious intent and belief were discovered to be inherent motivating factors driving a growing preference for organic food over the conventional grown food, In contrast, factors such as health and government support policy failed to show any significant influence towards organic food purchase intention amongst the university students.